Identifying the profile of the Skin Tears patient in hospitalization - contributions to care planning (Research, Society and Development, 2022)
Objective: To identify the profile of patients with Skin Tears in hospital admission and propose the development of a digital instrument for nurse assessment. Method: Observational, cross-sectional study, in a university hospital in the city of São Paulo. The collection was performed in the months of September 2021 to April 2022, with quantitative analysis. Results: The sample was composed of 34 patients, with a prevalence of men, with a mean age of 66.3 years, 44% admitted to the ICU with a higher predominance of cause of hospitalization for infection. In this study, 17 patients had hypertension and 74.7% used a cotinous mixture of medications. Among the patients, 79.4% had edema, 41.2% performed body hydration, 88.2% did not wander, 94% required help to change their decubitus, and 26 patients were bedridden. Laboratory tests indicated changes in C-reactive protein, hemoglobin, hematocrit, and platelets. The most prevalent medical device was central venous catheter/dialysis (64.7%), pressure injury was present in 42 patients (123.5%) and the most prevalent friction injury, using the STAR classification, was class 1 a (23.5%), being present in half of the patients in the upper limbs (50%). Conclusion: In the present study, it was possible to identify the main characteristics of the patient with Skin Tears and the nurse's need for information and knowledge about this type of injury to prevent its development through prevention and perform the appropriate treatment.